A global health equity agenda for the G8 summit. Issue 7490 (3rd March 2005) - Labonte, Ronald; Schrecker, Ted; Gupta, Amit Sen
Abstract : The G8 summit in July could be used to enable developing countries to meet the millennium development goals. What should world leaders commit to?